PERAN WANITA SEBAGAI PENCARI NAFKAH KELUARGA DALAM PERSPEKTIF HUKUM ISLAM - Luluk Shoviana; Zahrotun Navish Abdillah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2019)
This study aims to determine the provisions of the role of women as female workers in the perspective of Islamic law, and the provisions of the role of women as female workers from the perspective of positive Indonesian law. The type of research used is field research using a qualitative approach. The data collection instrument use is the interview and observation studies. This study uses descriptive analytic. The results of this study indicate that The role of women as female workers in the perspective of Islamic law is basically permissible, due to seeking the living to fulfill the means of life is the right and obligation of both men and women as long as a wife does not neglect her obligations to her husband and children. The role of women as female workers in the perspective of positive Indonesian law is also permissible, because a woman is able to carry out activities both inside and outside the employment relationship to produce goods or services to meet their own needs and community needs.